Kegiatan berbagi takjil menjelang adzan maghrib dalam peran penguatan kepedulian sosial sesama di Jalan Kolonel Sugiono Kureksari Waru Sidoarjo - Naillah Bintang Khoirunnisah (Penamas: Journal of Community Service, 2026)
The tradition of sharing takjil is a deeply rooted socio-religious practice among Muslim communities in Indonesia. This community service activity aimed to foster social awareness by distributing free takjil to residents and road users on Jalan Kolonel Sugiono, Kureksari Village, Waru District, Sidoarjo Regency, before the breaking of the fast. This activity employed the ABCD (Asset-Based Community Development) approach, a community empowerment framework that focuses on identifying and exploring the community's assets and resources. During the implementation stage, students actively participated by approaching residents and road users in the area and distributing takjil directly, without discrimination based on social background. The results showed a positive response from the community, as reflected in the recipients' enthusiasm and the community’s acceptance of the sharing activity before iftar. However, the activity still had several limitations, particularly in terms of distribution management and the limited number of takjil packages available. Therefore, similar activities in the future should be planned more systematically and involve more stakeholders to ensure the benefits reach a wider community.